Community dynamics under environmental extremes: coastal plain wet prairie in a natural state and under restoration - Dixon, Cinnamon M.; Flaherty-Walia, Kerry E.; Snyder, Richard A. (Plant ecology, 2021)
Ecological restoration is increasingly employed to restore degraded or destroyed ecosystems and evaluation of restoration success requires that natural community dynamics be understood. Wet prairies in the Southeast US have diverse plant communities subject to disturbances including fire, drought, flooding, tropical storms, and freezes. This habitat covers a fraction of its former range and reversing that trend requires ecological restoration; but, long-term data on the dynamics of this system are rare. We analyzed a 12-year plant community composition dataset from a fire-maintained Gulf of Mexico Coastal Plain wet prairie to characterize plant community dynamics and identify indicator species. The site was compared to a nearby wetland mitigation project attempting to restore a wet prairie that had been converted into slash pine (Pinus elliottii) plantation. The reference site had higher species richness, was dominated by Aristida spp., and was stable despite extreme climatic conditions. The restoration site transitioned from dense pine and understory canopy to an open, grassy community, but did not follow a trajectory toward the reference state. Restoration efforts were impeded by woody debris, accumulated duff, soil disturbance from logging, and storm surge from hurricanes. Continued application of prescribed fire and decomposition activity should remove the organic matter and promote establishment of wet prairie species, but on a longer time scale than expected. Although the pine plantation did not return to a typical wet prairie during the study period, the record of community dynamics of the reference wet prairie provides information on the resilience of the habitat type under prescribed fire management, and serves as a reference for restoration efforts and management of this threatened habitat.